Sunday

July 13, 2014

July 13, 2014

Posted by **Anonymous** on Monday, December 9, 2013 at 12:57pm.

- MATH -
**SAM**, Monday, December 9, 2013 at 1:00pmY=2X+4

Y=2(3)+4

Y=6+4

Y=10

- MATH -
**X**, Monday, December 9, 2013 at 2:55pmHere, all you have to do is simply substitute (3) for the variable (x) in the equation. You can do this because all coordinates are of the form (x,y), and anything that takes the place of (x) in that form can be seen as equal to (x).

The working is shown below:

y = 2(3) + 4

y = 6 + 4

y = 10

As shown above, y = 10 when x = 3.

**Related Questions**

solution of an equation - can someone please give me an example of a solution of...

math ALGEBRA - Solve by graping the foll: A. 2X+Y=5 3X-Y=10 B.2X=Y+1 2X-Y=5 I ...

math - 1-AND PRODUCTION sum of roots of the equation :X²-X-6=0 2-FOR what values...

Math - What are Fractions? Numbers equal to one integer divided by another ...

Math 4 (Count Ibilis) - Solve by factoring: One of the solutions to the ...

calculus - Use the Intermediate Value Theorem to prove that the equation has a ...

Math - Write the equation in standard form using integers. Can someone please ...

Algebra 1 - 23.what is the slope of a line parallel to a line represented by the...

Precalculus - Which of the following is a solution for the equation 1/485tan^2x...

Algebra II-Please check my solution - Solve by elimination method-thanks fro ...